Breeding management strategies adopted for dairy production under low-input smallholder farming systems of East Africa - Ojango, Julie M.K.; Kariuki, K.; Njehu, A.; Baltenweck, Isabelle (East Africa Dairy Development Project, 2010)
Designing and implementing sustainable breeding management programmes is one of the most practical means of improving efficiency in livestock production, particularly in developing countries. The success or failure of an improvement programme hinges strongly on the compatibility of the programme with the objectives of the farming community targeted. This report contributes to a better understanding of the pre-existing breeding management strategies within cattle-keeping communities of the EADD project sites, and will help in the definition of appropriate breeding objectives and the design and implementation of a sustainable breeding programme for the small holder farmers. The farmers in the three countries rear a variety of cattle, classified into two broad categories as exotic and indigenous breed-types. More exotic breed-types are reared in Kenya than in Rwanda and Uganda. Among the exotic breed-types reared, the Holstein-Friesian is most popular in all the countries. The Ayrshire breed-type is also very popular in Kenya. In Uganda, the most common type of cattle are the indigenous Ankole, while in Rwanda, various crosses are popular. There are no written records available on individual animals. The breed-type of animal raised on a farm is significantly influenced by the age and level of education of the head of the household. On average, in households headed by older and more educated people, there are more exotic breed-types of animals reared. These households also live in areas with higher human population density. Farmers implement some form of controlled mating, either to minimize inbreeding, or to seek better mates among the population available. There is also some degree of planned cross-breeding taking place in all the countries. On most farms, animals calved down for the first time when they were above 27 months old, with exotic animals calving at a younger age than indigenous ones. Calving intervals were on average longer in Kenya than in the other countries. Indigenous animals tended to calve for the first time at close to four years of age in Uganda where malnutrition was noted as a key factor requiring to be addressed. More than 10% of the animals on farms within the three countries were culled in a 12 month period with a replacement rate of less than 5%, implying an overall reduction in herd size over time. The most desirable traits in exotic animals raised in all three countries were high milk production and good body conformation. In the indigenous breed-types reared, adaptability was the most important trait in all the countries. An interesting observation was that not all farmers raised the breed-type of animal that they admired most. It was clear that the farmers were knowledgeable to some degree on several aspects related to selective breeding of animals. To effect change in the existing production systems, in addition to availing improved breeding materials at an affordable cost, capacity development using simplified messages targeted to address specific knowledge gaps concerning breed choice, reproduction and selection decisions is required.